CAFFEIC ACID PHENETHYL ESTER DECREASES THE LEVEL OF S-100B PROTEIN AFTER MIDDLE CEREBRAL AFTER OCCLUSION IN RABBITS - Serarslan, Yurdal; Bal, Ramazan; Altug, Muhammed Enes; Kontas, Tuenay; Melek, Ismet Murat (Univ Karachi, 2009)
Effects of caffeic acid phenethyl ester (CAPE) on the serum S-100B levels were studied as an index for brain damage after permanent middle cerebral artery (MCA) occlusion in rabbits. Twenty rabbits were divided into four groups (n=5): control, sham, non-treatment and CAPE. The right MCA was occluded using a microsurgical procedure with bipolar coagulation and was then transected in non-treatment and CAPE groups. The rabbits in the sham group underwent a surgical procedure but the MCA was not occluded. No surgery was performed in the control group. CAPE was administered after MCA occlusion at the dose of 10 mu g/kg, once a day intraperitoneally for 7 days in the CAPE group. Serum S-100B levels were determined on days 1, 2, 4 and 7. Serum S-100B level was significantly increased following permanent MCA occlusion. Posttreatment of CAPE significantly reduced the serum S-100B level. This study demonstrated that CAPE is capable of attenuating increased serum S-100B level induced by MCA occlusion in rabbits. CAPE may be useful as a neuroprotective agent.
Keywords: Brain; caffeic acid phenethyl ester; CAPE; experimental stroke; middle cerebral artery occlusion; MCA; S100B